Ultrasound imaging and therapy - Fenster, Aaron, 1947-; Lacefield, James C. (Imaging in medical diagnosis and therapy., 2015)
Up-to-Date Details on Using Ultrasound Imaging to Help Diagnose Various DiseasesDue to improvements in image quality and the reduced cost of advanced features, ultrasound imaging is playing a greater role in the diagnosis and image-guided intervention of a wide range of diseases. Ultrasound Imaging and Therapy highlights the latest advances in using ultrasound imaging in image-guided interventions and ultrasound-based therapy. The book presents current and emerging techniques, identifies trends in the use of ultrasound imaging, and addresses technical and computational problems that need to be.